An Investigation on The Adaptation of Traditional Naxi Costume Elements into Contemporary Clothing - Qiu Qilu; Lee, Lilian Shiau Gee; Victor B. Pangayan (Penerbit Universiti Malaysia Sabah, 2024)
The Naxi ethnic group in China has a rich and extensive history. Their remarkable traditional attire has been recognised and designated as a "living" culture by the United Nations (Wang, 2017). Nevertheless, due to shifting trends and lifestyles, contemporary society, particularly the younger generation, is progressively disregarding traditional attire. As a result, designers have incorporated diverse influences, such as blending contemporary ideas with traditional cultural features, in order to create "modern clothing" that may endure and gain international recognition while preserving the legacy of fashion. Hence, it is imperative to foster the development of Naxi heritage, just as it is done for other ethnic groups. This includes the crucial integration of Naxi motive aspects into contemporary culture. This study aims to investigate the attributes of traditional clothing elements of the Naxi ethnic group. It will employ questionnaires to examine the community's perspectives and preferences regarding the innovative design of Naxi clothing elements. The objective is to both preserve the cultural essence of these elements and achieve innovative designs. By doing so, Naxi clothing can showcase the allure of new culture and art.